Analysis of the Effect of Cationic and Anionic Surfactants and Polymer Additives on the Water-Oil Interface in Enhanced Oil Recovery: A Molecular Dynamics - Naibaho, Frans Nicolas P.; Ar-Raihan, Muhammad Hasbi; Adharis, Azis; Ratri, Paramita Jaya; Mayangsari, Tirta Rona (UIR PRESS, 2024)
The high demand for petroleum requires a more efficient production process. Enhanced Oil Recovery (EOR) technology with chemical injection methods can optimize oil production in reservoirs. To understand the properties of these chemicals, analysis at the atomic level is necessary. This research utilizes molecular dynamics simulations using the Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) to analyze diffusion coefficients and Interface Formation Energy (IFE) values. Surfactants such as Dodecyl Trimethylammonium Bromide (DTAB), Sodium Dodecyl Sulfate (SDS), and Polyacrylic Acid (PAA) polymer are studied. Results indicate that DTAB, SDS, and PAA stabilize the water-oil system, shown by lower IFE values: -48.53, -178.33, and -231.78 kcal/mol, respectively. DTAB increases the diffusion coefficient of dodecane from 0.01 Å²/ps to 0.039 Å²/ps. SDS and PAA increase water diffusion coefficients from 0.0094 Å²/ps to 0.0097 Å²/ps (with SDS) and 0.0179 Å²/ps (with PAA).